Are Private Equity Investors Good or Evil? - Oleg Badunenko; Nataliya Barasinska; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The paper investigates the motives of activity (entry and exit) of Private Equity (PE) investors in European companies. Investment of a PE firm is not viewed unambiguously. First, it is claimed that PE investment is made for the sake of seeking shortterm gains by taking control and utilizing the company's resources. Second, a PE firm invests because of prior identification of chances to add value to the company. We attempt to resolve these two conflicting conjectures. We use the Bureau van Dijk's Amadeus database of very large, large and medium-sized European companies. Our major results can be summarized as follows. First, PE firms are less willing to enter the firm if there is already a blocking majority, and they are more likely to leave the firm if control cannot be overtaken. Second, less mature firms are less able to lure a PE firm to invest, thus indicating a safe strategy of PE investors. Third, we do not find empirical evidence that a PE investor comes in to strip a firm of its equity. On the other hand, PE investors are likely to leave the company if it deteriorates in terms of returns and cash. Finally, when comparing the activity of PE and other financial investors, we find essential differences in choosing the field and environment of activity.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: M14; G24; G34; 330; Private equity financing; leverage; corporate finance